Apparent L-Falsity and Actual Logical Structures - López-Astorga, Miguel (Problemos, 2020)
In 2012, Orenes and Johnson-Laird found interesting results from the cognitive point of view but problematic if analyzed under methods such as the semantic one of extension and intension presented by Carnap. The main difficulty in this way is that Orenes and Johnson-Laird showed that people tend to accept, in the case of certain inferences, conclusions that, by themselves, are, according to the aforementioned semantic method, false in absolutely all of the state-descriptions that can be imagined. However, in this paper, a way to overcome that difficulty is proposed. That way is based upon the idea that the real logical forms of the conclusions accepted by the participants in Orenes and Johnson-Laird’s experiments were not the apparent ones, but they corresponded to other very different structures that can be true in some state-descriptions.